Um olhar sobre os colegiados dos territórios da cidadania no Pará - PIRAUX, Marc (2015)
Territorial policies and in particular the Territories of Citizenship in Brasil are interesting institutional innovations. Evaluating and improving them require an analysis of the different mechanisms of public action and their practical consequences on the resulting territories. In the state of Para, strong relationship exists between territorial dynamics and functioning of Territorial Joint Committee of Territories of Citizenship. analyzed with the levei of participation, with efficiency of the governance and with implementation of projects investment. General and specific problems and positive aspects of the institutional arrangements are explained. Methodological and development perspectives are given to improve the program.